Measurement of Optic Nerve and Optic Nerve Sheath Diameter in MRI Brain - Joshi, Sweta; Paudel, Sharma; Pandey, Durga; Kayastha, Prakash (Journal of Institute of Medicine Nepal, 2023)
Introduction Many diseases affect the size of the optic nerve and optic nerve sheath, measurement of which is important for the diagnosis and treatment of many pathologies of the brain and orbit. This study aimed to measure the diameter of the optic nerve and optic nerve sheath in MRI brain examinations. We also studied their variation according to age, gender, and laterality. Methods This cross-sectional, quantitative study was performed in the Radiology Department of Tribhuvan University Teaching Hospital (TUTH). The diameter of the optic nerve and optic nerve sheath were measured in the T2 weighted Dixon Turbo Spin Echo axial images. The diameter was measured at the level of 3mm and 8mm behind the eye globe. The study was completed over a period of 3 months (August 2023 to October 2023). Results The mean diameters of the optic nerve were 2.187±0.35 mm/2.14 ± 0.35 mm at 3 mm behind the eye globe and 2.056 ± 0.334 mm/2.11 ± 0.35 mm at 8 mm behind the globe for the right/left sides respectively. The optic nerve sheath of the right/left sides measured 4.50 ± 0.60 mm/4.46 ± 0.56 mm at 3 mm behind the eye globe and 4.16 ± 0.50 mm/ 4.14 ± 0.47 mm at 8mm behind the eyeball. Conclusion The measurements for the diameter of the optic nerve and optic nerve sheath complex were similar in both the right and left eyes. There was no significant difference in optic nerve and optic nerve sheath diameters with the age and gender of the participants.